PENGARUH INKLUSI KEUANGAN, PENGETAHUAN KEUANGAN DAN TINGKAT PENDIDIKAN TERHADAP PERILAKU KEUANGAN PADA PELAKU UMKM DI KECAMATAN RANTEPAO KABUPATEN TORAJA UTARA - Lusdani, Westerini; Panimba, Winta; Herlisya, Herlisya (ITB AAS Indonesia Surakarta, 2025)
The Influence of Financial Knowledge, Financial Inclusion and Education Level on Financial Behavior among MSMEs in Rantepao District, North Toraja Regency. This research aims to find out whether the variables Financial Knowledge, Financial Inclusion, and Education Level have an effect on Financial Behavior. The type of research used in this research is quantitative descriptive. This research used a sample of 71 MSMEs in Rantepao District. The results of this research show that partially Financial Knowledge has a significant effect on Financial Behavior in MSMEs in Rantepao District, this can be seen in the results of the t test where the sig value is 0.037 < 0.05, partial Financial Inclusion has no significant effect on Financial Behavior For MSMEs in Rantepao District, with a value of sig. 0.857 > 0.05, while the level of education partially has a positive effect on the financial behavior of MSMEs in Rantepao District, a value of sig. 0.016.< 0.05 and simultaneously Financial Knowledge, Financial Inclusion, and Level of Education have a significant positive effect on Financial Behavior in MSMEs in Rantepao District. This can be seen in the results of the F test where the significance value is 0.004 < 0.05.